Effect of the Economic Crisis on Housing Market in Poland - Cymerman, Joanna; Cymerman, Wojciech (European Scientific Journal, ESJ, 2017)
The housing market is an important part of the economy and stays with her in close connection. On the one hand, affects macroeconomic variables by participating in the creation of gross domestic product (GDP), the share of the resource (national wealth), creating jobs, providing tax revenues, or providing the opportunity to unfreeze the capital. On the other hand, the phenomena and processes occurring in the economy can affect stimulating or inhibiting effect on the development of the housing market, in particular by: changes in interest rates on loans, changes in demand for surface or changes in the attractiveness of other capital investments. The publication is devoted to the issues of the impact of the economic crisis (started in Poland in 2009) on the housing market in Poland. The main objective of this paper is to examine the dynamics of downward trends in the residential property prices exemplified by a medium-size city. A hypothesis is made that the dynamics of the decline of residential property prices in the times of crisis is much poorer in medium-size cities than in large urban agglomeration. The study covers the quarters of 7.5 years between 2009 and 2016 (I. half) – 30 quarters. The findings of the study on the residential property market in Koszalin are presented in reference to the data on residential property markets in 17 Polish largest cities. presented the results of analyzes are part of the research conducted by the authors on the real estate market and its functioning.